Is Erasmus going green? The carbon footprint of European academic mobility and sustainability policies of European universities - Gabrielczak, Piotr; Sokołowicz, Mariusz E. (European Spatial Research and Policy, 2024)
The European Union has promoted academic mobility for almost half a century. A side effect of that has been a growing carbon footprint, as most academic mobility in Europe is done by air. Based on mobility data for 2014−2020, we analysed its spatial distribution and identified dominant destinations. Juxtaposing these results with research on higher education institutions’ environmental measures and policies, we have identified that the willingness to reduce the carbon footprint is emerging yet tenuous, and more declarative than actual. We recommend more decisive steps to reduce air travel within Europe, outlining the possibilities for carbon footprint reduction without harming European academic mobility itself.